2011
DOI: 10.1557/mrs.2011.71
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms as complex fluids

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
238
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(246 citation statements)
references
References 72 publications
7
238
1
Order By: Relevance
“…[1][2][3] Action potentials, osmotic flows, energy transduction, 4 and the stabilization of proteins are driven by ion concentration gradients across liquid films on hydrophobic biomaterials. 3,[5][6][7][8][9][10] Recent experiments in our laboratory revealed that ions interact specifically at the prototype airwater interface over separations that vastly exceed the range of direct electrostatic forces in any dielectric medium. 11 Such long-range specific ion effects (LR-SIE) may be triggered by electrostatic and electrodynamic forces, but it is obvious that they must be powered by other mechanisms, such as the thermal fluctuations intrinsic to fluid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Action potentials, osmotic flows, energy transduction, 4 and the stabilization of proteins are driven by ion concentration gradients across liquid films on hydrophobic biomaterials. 3,[5][6][7][8][9][10] Recent experiments in our laboratory revealed that ions interact specifically at the prototype airwater interface over separations that vastly exceed the range of direct electrostatic forces in any dielectric medium. 11 Such long-range specific ion effects (LR-SIE) may be triggered by electrostatic and electrodynamic forces, but it is obvious that they must be powered by other mechanisms, such as the thermal fluctuations intrinsic to fluid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The principles of soft condensed matter physics can be applied to understanding how bacterial aggregates form; cultures of non-motile bacteria are effectively colloidal dispersions, and many mechanisms that underlie the stability of colloidal dispersions will be relevant to bacterial cultures [17]. Polymers can contribute to the destabilization of colloidal dispersions via two generic mechanisms: polymer bridging and depletion attraction.…”
Section: Introductionmentioning
confidence: 99%
“…embedded in a hydrated polymeric mesh [90]. If the volume fraction φ occupied by the cells is high, greater than roughly 0.2-0.5, the mechanical response will be dominated by steric hinderance acting between the stiff cell walls, and an analogy with colloidal systems is possible [102]. More commonly, however, φ ≪ 1 and the response is determined by the interdispersed matrix which reacts via purely physicochemical mechanisms on times scales shorter than the cells' metabolic response.…”
Section: Molecular Origins Of Biofilm Mechanicsmentioning
confidence: 99%
“…The primary distinction from a recent review [39] is the focus here on constitutive modelling following an approach common to soft matter systems, i.e. solutions of macromolecules such as colloids, flexible and semi-flexible polymers, which have been recognised as an abiotic counterpart of biofilms with regards mechanical response [102]. A pragmatic benefit of deriving and validating quantitative models is their predictive capability, which can be used to guide the design of novel technologies targeting reduced biofilm-related infections, for instance water lines that minimise microbial spread.…”
Section: Introductionmentioning
confidence: 99%